Стапиците на автентичноста и идентитетот низ призмата на балканските стереотипи во Медена земја и Пред дождот - Ноневски, Вангел (Македонска Академија на Науките и Уметностите: Одделение за лингвистика и литературна наука, 2022)
This text provides an insight into Maria Todorova’s theory of Balkanism, as a basis for reading the stereotypes and the self-stigmatization in the Macedonian films Honeyland and Before the Rain. The Balkans, like Said’s Orient, are presented as a Western construct, usually not a reference of the region, but of a phantasm constantly filled with prejudice and negative identifications. The conclusion is that the cinematic representation of the fetishized rural Macedonian past, understood as a singular authentic identity, must be reckoned with.
Keywords: stereotype, self-stigmatization, Balkanism, authenticity, identity, postcolonialism, exoticism, cultural mediation